P16.12 BRAIN LOCATIONS INVOLVED IN BASELINE COGNITIVE FUNCTIONING OF PATIENTS WITH GLIOMA BEFORE THERAPY - Habets, E.J.J. (Oxford University Press, 2014)
INTRODUCTION: Cognition is often affected in patients with brain tumors. Apart from language function, direct tumor effects on discrete cognitive functions have barely been studied. In this study, we quantify baseline functioning in seven cognitive domains and identify brain locations involved in these cognitive domains using tumor localization maps (TLMs), which is a new approach. METHODS: Adult patients with glioma treated at the VU University Medical Center between 2006-2011 with available preoperative neuropsychological assessment were included. Cognition was tested for verbal memory, visuospatial memory, working memory, attention, executive functioning, information processing speed, and visuoconstructive abilities. Cognitive performance was compared to healthy controls, matched for age, sex, and educational level. Tumor volumes for TLMs were segmented on MRI fluid attenuated inversion recovery (FLAIR) hyperintense signal abnormality for low-grade gliomas, and MRI T1 contrast-enhanced abnormality for high-grade gliomas. For each cognitive domain, we applied TLMs to link cognitive performance with location throughout the brain at 1 mm resolution. Considerations for spatial dependence and multiple comparisons were taken into account. PRELIMINARY RESULTS: Seventy-four patients (7 with WHO grade I, 43 with grade II, 12 with grade III, and 10 with grade IV glioma, and 2 with other histology) were included so far. Mean age of patients was 40 years. Preoperative cognitive functioning was significantly impaired in five of seven domains compared to healthy controls. Most frequently affected were attentional function and working memory capacity (30% and 21% of patients, respectively). No differences in cognitive domain scores were observed between patients with low-grade and high-grade glioma. Tumor localization maps are currently being processed and statistically compared voxel-wise for each of the seven cognitive domains. Preliminary results of the TLMs demonstrate that performance in specific cognitive domains is associated with specific brain tumor locations. CONCLUSION: Empirical evidence on location of cognition can be used for optimizing brain tumor surgery and be integrated in counseling and cognitive rehabilitation for patients with newly-diagnosed glioma.